2016
DOI: 10.1038/oncsis.2016.76
|View full text |Cite
|
Sign up to set email alerts
|

Sharpin promotes hepatocellular carcinoma progression via transactivation of Versican expression

Abstract: Sharpin (Shank-associated RH domain-interacting protein, also known as SIPL1) is a multifunctional molecule that participates in various biological settings, including nuclear factor-κB signaling activation and tumor suppressor gene inhibition. Sharpin is upregulated in various types of cancers, including hepatocellular carcinoma (HCC), and is implicated in tumor progression. However, the exact roles of Sharpin in tumorigenesis and tumor progression remain largely unknown. Here we report novel mechanisms of HC… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

3
31
0

Year Published

2017
2017
2021
2021

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 30 publications
(34 citation statements)
references
References 31 publications
3
31
0
Order By: Relevance
“…Upregulation of SHARPIN in HCC [22] was confirmed in a previous study by our group [25] , in which SHARPIN expression was shown to be positively correlated with larger hepatic tumors, a higher histological grade, and therefore HCC progression. In recently published work, we examined the role of SHARPIN in the malignant phenotype characteristic of HCC [25] .…”
Section: Sharpin: Newly Identified Mediator Of Hcc Invasion and Progrsupporting
confidence: 66%
See 4 more Smart Citations
“…Upregulation of SHARPIN in HCC [22] was confirmed in a previous study by our group [25] , in which SHARPIN expression was shown to be positively correlated with larger hepatic tumors, a higher histological grade, and therefore HCC progression. In recently published work, we examined the role of SHARPIN in the malignant phenotype characteristic of HCC [25] .…”
Section: Sharpin: Newly Identified Mediator Of Hcc Invasion and Progrsupporting
confidence: 66%
“…Its expression is significantly higher in HCC and is correlated positively with SHARPIN expression. Knockdown of versican attenuates HCC invasion, which implicates versican in SHARPIN-mediated HCC invasion, and this relationship was confirmed in an in vivo tumor model [25] . Versican transcription is regulated by T-cell factor (TCF) [28][29] .…”
Section: Sharpin: Newly Identified Mediator Of Hcc Invasion and Progrmentioning
confidence: 61%
See 3 more Smart Citations